Effect of Boiling Duration on the Antioxidant Activity of Purple Eggplant (Solanum melongena L.) Using the DPPH Method - Br Brahmana, Ana Stela Yofani; Ompusunggu, Henny Erina Saurmauli; Sihombing, Jenny Ria (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
Background: Excessive free radicals in the body can cause oxidative stress and trigger various diseases. Antioxidants play a crucial role in neutralizing free radicals. Purple eggplant (Solanum melongena L.) is a natural source of antioxidants that has a high anthocyanin content. The boiling process is essential for preparing purple eggplant, as it can affect its antioxidant activity. Methods: This study was a controlled laboratory experimental design, observing the antioxidant activity of boiled purple eggplant extracts at durations of 4 minutes, 8 minutes, and 12 minutes, with concentrations of 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm. The qualitative test was conducted to detect the presence of flavonoids, while the quantitative test was performed using the DPPH method with a UV-Vis spectrophotometer and repeated three times. Results: The flavonoid test indicated that purple eggplant contains antioxidant compounds, as shown by the color change from brick red to golden yellow. The IC50 values of boiled purple eggplant were 152 ppm (4 minutes), 110 ppm (8 minutes), and 130 ppm (12 minutes). Conclusion: The antioxidant activity of purple eggplant (Solanum melongena L.) measured using the DPPH method was categorized as moderate, with the highest antioxidant activity observed at 8 minutes of boiling, indicated by the lowest IC50 value of 110 ppm. In comparison, the IC50 values at 4 and 12 minutes of boiling were 152 ppm and 130 ppm, respectively. These findings suggest that boiling duration affects antioxidant activity, with 8 minutes representing the optimal boiling time for preserving antioxidant compounds in purple eggplant.